Pertunjukan Wayang Kulit dan Ritual Keagamaan (Studi Tentang Eksistensi Wayang Kulit di Bali Utara) - I Kadek Bhaswara Dwitiya; I Putu Ardiyasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Balinese shadow puppet shows always go hand in hand with religious ritual activities. In religious ritual activities in North Bali, it always involves wayang performances as an important part of completing ceremonies in Niskala and Sekala. In Niskala, Tirta Pewayangan is believed to be Pangruwatan, while Sekala, Krama or people who watch puppets are entertained and Kelangen (fascinated). However, since the golden age of wayang in the 80s until the early 2000s, wayang as a show made Kelangen less and less. Although in the order of religious rituals in North Bali, all Yadnya ceremonies use wayang kulit, but often puppets are present without the audience, or only watched by parents. This study wants to see the existence of Wayang Kulit performances in religious rituals in North Bali. To explain the existence of shadow puppet shows in religious rituals in North Bali, a phenomenological approach is used which encourages researchers to empty themselves from previous knowledge. Data were collected by participatory observation and in-depth interviews to obtain accurate data. The results show that the existence of religious ritual puppet shows in North Bali is presented in a simple way with a conventional North Balinese style show pattern. Wayang Kulit performances in North Bali are related to religious rituals, such as ceremonies for death, marriage, birth (otonan, three months) and the ceremony of the god yadnya. This is supported by the belief inherited by the senior officials in each family who have a ceremony